FORMULATION, EVALUATION AND OPTIMIZATION OF AMLODIPINE BESYLATE MELT IN MOUTH TABLETS PREPARED BY DIRECT COMPRESSION METHOD USING NATURAL AND SYNTHETIC SUPER DISINTEGRATING AGENTS. - S.JANAKIDEVI, (International Journal of Pharma and Bio Sciences, 2014)
The objective of the present study was to formulate Melt in Mouth Tablets of amlodipine besylate by comparing natural (Modified Tragacanth Gum) and synthetic polymers (Crospovidone) as super disintegrating agents to achieve quick onset of action, to increase water uptake with in shorter wetting time and there by decrease the disintegration time of the tablets by simple and cost effective direct compression technique. Amlodipine Besylate is a Calcium channel blocker used in the treatment of hypertension and angina. Formulations FMT1-FMT5 are prepared with Modified Tragacanth Gum, FCP1-FCP5 are prepared with Crospovidone. Pre, post-compression parameters were evaluated, the results were within specifications. When compared all ten formulations, FMT5 and FCP5 shows better results. Therefore formulation FMT5 and FCP5 was selected as the optimized formulations as it showed good in-vitro disintegration time, in-vitro drug release, wetting property. When an increase in the concentration of super disintegrating agent (natural, synthetic) improves the drug release.